(untitled) (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1953)
Studies on the application of small doses of procaine (Scurocaine 5 and 9 per cent) in the peridural (epidural) anesthesia in dogs, have been carried out. This technique has shown very good results as far as anesthesia conditions are concerned and a lot of advantages when in comparison to the findings of others authors who have worked on the same subject.